Development of Flipbook Learning Media on the Topic of Regional Economic Conditions for Fifth Grade Elementary School Studentsateri Kondisi Perekonomian Daerah kelas V SD - Sianipar, Putri SR; Thesalonika, Emelda; Tambunan, Janwar; Aren, Ease (PT. Anagata Sembagi Education, 2026)
This study aims to develop a digital flipbook-based learning media on regional economic conditions and determine its feasibility for fifth-grade elementary students. The research was motivated by low student learning interest and the limited use of digital media in IPAS learning. This study employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The data were collected through expert validation questionnaires (material, language, and media experts) and responses from teachers and students, analyzed using a Likert scale. The results showed that the developed flipbook media was categorized as very feasible, with material expert validation at 93%, language expert at 91%, and media expert at approximately 93%. Teacher responses reached 92% and student responses 89%, both categorized as very feasible. Therefore, the digital flipbook learning media is suitable as an alternative learning tool in elementary schools.